(untitled) (JURNAL ADMINISTRASI PUBLIK, 2016)
Abstrak: The system of Licensing and Investment information services Electronically (SPIPISE) is the innovation of public service that aims to bring about the licensing service and non-licensing better. The system of Licensing and Investment information services electronically allows investors to do simply licensing arrangements, cheap, efficient, and predictable. The system of Licensing And Investment information services Electronically also provides convenience for officers of the capital investment Coordination Agency (BKPM) and Integrated Service of one door (PTSP) to do the validation and get data in processing the application for the investment into capital investment coordination board authority nor one door Integrated Services. The system of Licensing and Investment information services electronically has three (3) main menu; information capital investment, capital investment and Supporting Services. Implementation of the system of Licensing and Investment information services electronically viewed from 4 implementation theory according to Edward III, namely: communication, resources, attitudes and bureaucratic structure. This research uses descriptive method of kualitatif approach through an in-depth interview to 10 (ten) informants, observation and search additional documents in the form of a list of guidelines for interviewing, recording device and stationery to write. The results showed that in general the system of Licensing and Investment information services electronically has not gone well. Key words: Implementation of Licensing and Investment Information Service PENDAHULUAN Menghadapi Era Globalisasi yang penuh dengan